Evaluation of an educational intervention based on health belief model on beta thalassemia carrier and final suspects couples - Nourdin Saeedi Kia; Khdabaakhsh Karami; Hashem Mohamadian; Amal Saki Malehi (Wolters Kluwer Medknow Publications, 2018)
Introduction: Beta-thalassemia is the most severe form of thalassemia major in which where the person needs regular blood transfusions and medical cares. The genetic experiment of prenatal diagnosis (PND) has been effective in the diagnosis of fetus with thalassemia major. This study was aimed to evaluate educational interventions on perceived susceptibility, perceived severity, perceived benefits, perceived barriers, cues to action and self-efficacy in beta-thalassemia carriers and suspected couples on doing a PND genetic test in Andimeshk. Materials and Methods: In this quasi-experimental study, 224 beta-thalassemia carriers and suspected couples were randomly assigned to intervention and control groups. The data were collected using a researcher-made validated questionnaire using the self-administrated method. Before the intervention, questionnaires for both groups were completed, and then, an educational intervention was done for the intervention group during a month in four sessions for 30 min. After 2 months, the questionnaire was completed again by both groups. Data were analyzed using SPSS software version 20. Results: There was no significant difference in the mean score of health belief model (HBM) variables and behavior between intervention and control groups before intervention (P < 0.05). However, after the educational intervention, the significant statistical difference in the mean score of perceived sensitivity, perceived severity, perceived benefits, perceived barriers, guidance for action, self-efficacy, and behavior of PND β-thalassemia genetic tests was observed between the intervention and control groups. (P < 0.001). Conclusion: Educational programs based on HBM can increase HBM constructs, behavior, and self-efficacy of beta-thalassemia carrier couples for doing beta-thalassemia PND.